Incidence of Lesions of Organs and Systems in Iron Deficiency Anemia in Children and Its Predictive Significance in the Development of Diseases of Internal Organs - Albert Giliazev (Journal of Global Pharma Technology, 2019)
This article deals with the study of the incidence of somatic pathology in children with iron deficiency anemia. It is shown that children with anemia more often have respiratory pathology, and less often - endocrine diseases. Somatic pathology is almost equally diagnosed in boys and girls and predominates in young children. The authors established the importance of iron deficiency anemia in the development of diseases of internal organs, determining the time of formation and nature of the disease, as well as increasing the risk of involvement of a number of organs and systems in the pathological process. Keywords: Iron deficiency anemia, children.